2007
DOI: 10.1537/ase.050308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of erect bipedal standing on the morphology of rat vertebral bodies

Abstract: An osteometric approach was used to demonstrate the relationship between vertebral body morphology and bipedal standing using 17 rats, which had been divided into control and exercise groups. Only the latter group (n = 9) performed a series of bipedal standing exercises using operant conditioning. Statistical analysis was conducted to allow for inter-group comparisons with respect to six linear dimensions and five indices for each of the 24 vertebral bodies, from the third cervical through the last lumbar vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The Jacobian matrix is calculated in equation ( 4). According to the principle of virtual work [21], we perform virtual displacement on the end effector, and since the sum of the virtual work is 0 we can promptly arrive at equation (5). The joint torque can be calculated from this virtual force, as shown in equation ( 6):…”
Section: Virtual Model Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jacobian matrix is calculated in equation ( 4). According to the principle of virtual work [21], we perform virtual displacement on the end effector, and since the sum of the virtual work is 0 we can promptly arrive at equation (5). The joint torque can be calculated from this virtual force, as shown in equation ( 6):…”
Section: Virtual Model Controlmentioning
confidence: 99%
“…In the 1980s, Rodman and McHenry [1], suggested that bipedal walking this form of locomotion liberated the remaining limbs and enabled humans to obtain better visions, use tools, and better access to food, which were conducive to survival. Humans, birds, monkeys [2,3], dogs, rats [4,5] and lizards [6][7][8] can learn to walk in two of their limbs. By contrast, hexapodal bipedalism can only happen to certain animals under several specific conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These epigenetic responses, using the term in its original, broad sense, promote the incorporation of altered modules into an integrated, functional phenotype (Hallgrímsson and Hall 2011 ), and create the potential for adaptive phenotypic plasticity. Examples are increasingly abundant, perhaps the most famous still being Slijper’s goat, born bipedal and whose unusual posture was evidently accommodated by other aspects of the musculoskeletal and nervous system (Rachootin and Thomson 1981 ; West-Eberhard 2003 ; for references to controlled experiments on other mammals, see Shi et al 2007 ). Such instances are not claims about specific evolutionary transitions but illustrate the latent potential to accommodate heritable changes in one system through epigenetic responses of other systems.…”
Section: The Origin Of Variationmentioning
confidence: 99%
“…In the lumbar region, the ventral vertebral body height is always bigger than the dorsal height, which emphasizes the lordotic shape of the lumbar region (Nissan and Gilad, 1986). It has been shown that bipedally conditioned rats also show a diminution in ventral wedging at lumbar levels, indicating this wedging is related to the upright posture causing a greater load from body weight (Shi et al, 2007). The bodies of the lumbar vertebrae show a significant trend toward lowering and broadening with age (Ericksen 1978a,b).…”
Section: The Vertebral Bodymentioning
confidence: 99%